White Birch, Red Hawthorn : A Memoir - Murphy, Nora (Book collections on Project MUSE., 2017)
""This is conquered land." The Dakota woman's words, spoken at a community meeting in St. Paul, struck Nora Murphy forcefully. Her own Irish great-great grandparents, fleeing the potato famine, had laid claim to 160 acres in a virgin maple grove in Minnesota. That her dispossessed ancestors' homestead, The Maples, was built upon another, far more brutal dispossession is the hard truth underlying White Birch, Red Hawthorn, a memoir of Murphy's search for the deeper connections between this contested land and the communities who call it home. In twelve essays, each dedicated to a tree significant to Minnesota, Murphy tells the story of the grove that, long before the Irish arrived, was home to three Native tribes: the Dakota, Ojibwe, and Ho-Chunk. She notes devastating strategies employed by the U.S. government to wrest the land from the tribes, but also revisits iconic American tales that subtly continue to promote this displacement--the Thanksgiving story, the Paul Bunyan myth, and Laura Ingalls Wilder's Little House books. Murphy travels to Ireland to search out another narrative long hidden--that of her great-great-grandmother's transformative journey from North Tipperary to The Maples. In retrieving these stories, White Birch, Red Hawthorn uncovers lingering wounds of the past--and the possibility that, through connection to this suffering, healing can follow. The next step is simple, Murphy tells us: listen"--